Demand Reduction in Multi-Unit Auctions: Evidence from a Sportscard Field Experiment: Reply - Engelbrecht-Wiggans, Richard; List, John A; Reiley, David H (American Economic Review, 2005)
Demand Reduction in Multi-Unit Auctions: Evidence from a Sportscard Field Experiment: Reply by Richard Engelbrecht-Wiggans, John A. List and David H. Reiley. Published in volume 95, issue 1, pages 472-476 of American Economic Review, March 2005